The Impact of Overweight and Obesity in Early Pregnancy on Maternal and Fetal Outcome - Giri, Amrita; Joshi, Anshumala; Upreti, Manita (Nepal Medical College Journal, 2022)
The recent increase in prevalence of overweight and obesity in pregnancy has become a major public health problem as it is associated with increased risk of obstetric and neonatal complications. A hospital based observational comparative study was done on women attending obstetrics and gynecology outpatient department of a tertiary care hospital in Kathmandu from September 2021 to January 2022 after taking ethical clearance from Institutional Review Committee. A total of 113 overweight/obese women in first trimester of singleton pregnancies and similar number of women with normal BMI were recruited for the study and followed throughout pregnancy for the development of maternal complications like gestational hypertension, gestational diabetes mellites, antepartum hemorrhage, preterm labor and postpartum hemorrhage. The neonatal outcome compared were birth weight, low Apgar score at birth and NICU admission. Maternal overweight/obesity as compared to normal BMI was associated with increased risk of gestational diabetes mellites (RR 2.06, 95% CI: 1.2 to 3.52; P value = 0.006), gestational hypertension (RR 2.2, 95% CI: 1.09 to 4.43; P value = 0.02) and caesarean delivery (RR 1.81, 95% CI: 1.28 to 2.55; P value = 0.004). The risk of primary postpartum hemorrhage was also increased in overweight/ obese women than in normal weight women (RR 2.8, 95% CI: 1.04 to 7.51; P value=0.03). In neonatal outcomes, the mean birth weight (3.18 + 0.54 kg vs 2.9 + 0.33kg, P value < 0.001) and admission to NICU (28.3% vs 10.61%, P value = 0.008) were significantly higher in overweight/ obese women. Maternal overweight/obesity in early pregnancy is associated with higher risk of adverse pregnancy and neonatal outcome.